PROBLEMS OF DEVELOPMENT OF THE FINANCIAL SYSTEM OF UKRAINE - Ustynova, Iryna; Savliva, Nataliia; Bardachevska, Anastasiia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Objective: to investigate the problematic issues of legal regulation of certain economic innovations and identify trends in the financial system of Ukraine. Research methods: research is conducted using a system of general and special scientific methods of cognition, which provide an objective analysis of the subject. Objectivity, value and structural-systemic approaches, as well as the use of logical methods, including analysis and synthesis, comparison, generalization, are important when studying this aspect. Results: the main features and problematic aspects of the introduction of new economic and legal forms and categories in the financial system of Ukraine are identified. Discussion: current state, peculiarities of formation and search for prospects for further development of Ukraine's financial system, experience of EU countries in implementing the basics of cryptocurrency regulation in the legal framework, as well as reducing workload, changing the system, unconditional income, new business programs, law on virtual assets, innovations for enterprises. At the present stage of formation of the financial system of Ukraine, the implementation of the program of socio-economic development of the policy of integration processes is envisaged. The purpose of integration processes in the financial policy of Ukraine is cooperation with various international organizations and financial institutions. Yes, it is important to work with international organizations such as the European Union, the Customs Union, the WTO, the United Nations, and financial institutions such as the IMF and the World Bank. It is also necessary to work on the adaptation of Ukrainian financial legislation to European requirements. In addition, Ukraine's financial policy should take into account external and internal factors of development in modern conditions. In addition, the problem of instability of Ukraine’s financial system, which is related to the country’s external debt dependence, is significant. In turn, the issues of stabilization and rehabilitation of the financial system of Ukraine are currently the most pressing issues for the state. Today, in the conditions of war, the creation of real starting preconditions for the structural restructuring of the economy and the resumption of the investment process has become urgent. It should be added that the financial system contributes to the construction of effective financial policies aimed at economic growth and improving the welfare of the population. That is why the creation of a perfect financial system of the state is one of the main conditions for the functioning of the economy.